WHO standards-based tool to measure women’s views on the quality of care around the time of childbirth at facility level in the WHO European region: development and validation in Italy - Marzia Lazzerini; Benedetta Covi; Emanuelle Pessa Valente; Chiara Semenzato; Ilaria Mariani; Ornella Lincetto; Moise Muzigaba; Giorgia Argentini (BMJ Open, 2022)
Objectives A comprehensive WHO standards-based tool to measure women’s perceived quality of maternal and newborn care (QMNC) in health facilities is needed to allow for comparisons of data across settings and over time. This paper describes the development of such a tool, and its validation in Italy.Design A multiphase, mixed-methods study involving qualitative and quantitative research methods.Setting Nine health facilities in Italy.Methods The questionnaire was developed in six phases: (1) Defining the scope, characteristics and a potential list of measures for the tool; (2) initial content and construct validation; (3) first field testing to assess acceptability and perceived utility for end-users (1244 women, 35 decision makers) and further explore construct validity; (4) content optimisation and score development; (5) assessment of face validity, intrarater reliability and internal consistency and (6) second field testing in nine maternity hospitals (4295 women, 78 decision-makers).Results The final version of the tool included 116 questions accounting for 99 out of the 350 of the extended lists of WHO Quality Measures. Observed face validity was very good, with 100% agreement for 101 (87%) questions and Kappa exceeding 0.60 for remaining ones. Reliability was good, with either high agreement or Kappa exceeding 0.60 for all items. Cronbach alpha values ranged from 0.84 to 0.88, indicating very good internal consistency. Acceptability across seven hospitals was good (mean response rate: 57.4%, 95% CI 44.4% to 70.5%). The questionnaire proved to be useful, driving the development of actions plan to improve the QMNC in each facility.Conclusions Study findings suggest that the tool has good content, construct, face validity, intrarater reliability and internal consistency, while being acceptable and useful. Therefore, it could be used in health facilities in Italy and similar context. More research should investigate how effectively use the tool in different countries for improving the QMNC.